News from the ICA Section on Archives and Human Rights - 2026-04 (April) - SAHR Newsletter Woking Group (ICA, 2026)

Input on the 2026 report of the Secretary-General on the Draft General Comment on the Application of the International Covenant on Economic, Social and Cultural Rights in Situations of Armed Conflicts - ICA Section on Archives and Human Rights (2026)

Archives and Emotions: International Dialogues Across Past, Present, and Future - Ilaria Scaglia and Valeria Vanesio (Bloomsbury Academic, 2026)
The work explores the mutually constitutive relationship between emotions and archives. The contributors consider how emotions have generated the very stuff of archives: the documents, the organization and construction of finding aids and collections, the archive’s creation and existence (or indeed, its destruction and/or absence).

News from the ICA Section on Archives and Human Rights - 2026-03 (March) - SAHR Newsletter Woking Group (ICA, 2026)

News from the ICA Section on Archives and Human Rights - 2026-02 (February) - SAHR Newsletter Woking Group (ICA, 2026)

News from the ICA Section on Archives and Human Rights - 2026-01 (January) - SAHR Newsletter Woking Group (ICA, 2026)

News from the ICA Section on Archives and Human Rights - 2025-12 (December) - SAHR Newsletter Woking Group (ICA, 2025)

Submission by the Section on Archives and Human Rights (SAHR) of the International Council on Archives (ICA) to the "call for inputs on the impact of mental health challenges on the enjoyment of human rights by young people" issued by the Office of the High Commissioner for Human Rights (OHCHR) - ICA Section on Archives and Human Rights (2026)

News from the ICA Section on Archives and Human Rights - 2025-11 (November) - SAHR Newsletter Woking Group (ICA, 2025)

News from the ICA Section on Archives and Human Rights - 2025-10 (October) - SAHR Newsletter Woking Group (ICA, 2025)

News from the ICA Section on Archives and Human Rights - 2025-09 (September) - SAHR Newsletter Woking Group (ICA, 2025)

News from the ICA Section on Archives and Human Rights - 2025-08 (August) - SAHR Newsletter Woking Group (ICA, 2025)

News from the ICA Section on Archives and Human Rights - 2025-07 (July) - SAHR Newsletter Woking Group (ICA, 2025)

News from the ICA Section on Archives and Human Rights - 2025-06 (June) - SAHR Newsletter Woking Group (ICA, 2025)

News from the ICA Section on Archives and Human Rights - 2025-05 (May) - SAHR Newsletter Woking Group (ICA, 2025)

News from the ICA Section on Archives and Human Rights - 2025-04 (April) - SAHR Newsletter Woking Group (ICA, 2025)

Archives and Traces of Migration - A Handbook of best practices - Štefanac, Tamara; Gilliland, Anne J. (ICARUS Croatia, 2025)

Refugee Rights in Records Framework - Refugee Rights in Records Initiative (2022)

News from the ICA Section on Archives and Human Rights - 2025-03 (March) - SAHR Newsletter Woking Group (ICA, 2025)

News from the ICA Section on Archives and Human Rights - 2025-02 (February) - SAHR Newsletter Woking Group (ICA, 2025)

News from the ICA Section on Archives and Human Rights - 2025-01 (January) - SAHR Newsletter Woking Group (ICA, 2025)

News from the ICA Section on Archives and Human Rights - 2024-11 (November) - SAHR Newsletter Woking Group (ICA, 2024)

Contribution of the ICA Section on Archives and Human Rights to the Call for inputs on 'Documentation of serious human rights violations in the context of transitional justice processes' issued by the UN Special Rapporteur on truth, justice, and reparation - ICA Section on Archives and Human Rights (2025)

News from the ICA Section on Archives and Human Rights - 2024-12 (December) - SAHR Newsletter Woking Group (ICA, 2024)

News from the ICA Section on Archives and Human Rights - 2024-10 (October) - SAHR Newsletter Woking Group (ICA, 2024)

News from the ICA Section on Archives and Human Rights - 2024-09 (September) - SAHR Newsletter Woking Group (ICA, 2024)

News from the ICA Section on Archives and Human Rights - 2024-08 (August) - SAHR Newsletter Woking Group (ICA, 2024)

News from the ICA Section on Archives and Human Rights - 2024-07 (July) - SAHR Newsletter Woking Group (ICA, 2024)

News from the ICA Section on Archives and Human Rights - 2024-06 (June) - SAHR Newsletter Woking Group (ICA, 2024)

News from the ICA Section on Archives and Human Rights - 2024-05 (May) - SAHR Newsletter Woking Group (ICA, 2024)

News from the ICA Section on Archives and Human Rights - 2024-04 (April) - SAHR Newsletter Woking Group (ICA, 2024)

News from the ICA Section on Archives and Human Rights - 2024-03 (March) - SAHR Newsletter Woking Group (ICA, 2024)

News from the ICA Section on Archives and Human Rights - 2024-02 (February) - SAHR Newsletter Woking Group (ICA, 2024)

News from the ICA Section on Archives and Human Rights - 2024-01 (January) - SAHR Newsletter Woking Group (ICA, 2024)

News from the ICA Section on Archives and Human Rights - 2023-12 (December) - SAHR Newsletter Woking Group (ICA, 2023)

News from the ICA Section on Archives and Human Rights - 2023-11 (November) - SAHR Newsletter Woking Group (ICA, 2023)

News from the ICA Section on Archives and Human Rights - 2023-10 (October) - SAHR Newsletter Woking Group (ICA, 2023)

News from the ICA Section on Archives and Human Rights - 2023-09 (September) - SAHR Newsletter Woking Group (ICA, 2023)

News from the ICA Section on Archives and Human Rights - 2023-08 (August) - SAHR Newsletter Woking Group (ICA, 2023)

News from the ICA Section on Archives and Human Rights - 2023-07 (July) - SAHR Newsletter Woking Group (ICA, 2023)

News from the ICA Section on Archives and Human Rights - 2023-02 (February) - Peterson, Trudy Huskamp (ICA, 2023)

News from the ICA Section on Archives and Human Rights - 2023-06 (June) - SAHR Newsletter Woking Group (ICA, 2023)

News from the ICA Section on Archives and Human Rights - 2023-05 (May) - SAHR Newsletter Woking Group (ICA, 2023)

Navigating Cultural Memory: Commemoration and Narrative in Postgenocide Rwanda - Mwambari, David (Explorations in Narrative Psychology, 2023)
Navigating Cultural Memory examines how a master narrative of the 1994 Genocide Against the Tutsi evolved into a hegemonic narrative both in Rwanda and globally. Identifying key actors who shaped and responded to the evolution and enforcement of the master narrative in the first two decades after the genocide and civil war ended, it engages with important questions about collective memory, trauma, and power following violent and divisive events. With chapters analyzing interviews the author collected, as well as other secondary sources, Mwambari charts how Rwandans from different backgrounds--who he identifies as Champions, Antagonists, and Fatalists of the master narrative--have responded to this event through language, physical symbols of memory, art, and traditional and new media.
Keywords: 2023-06 June

Archives and Transitional Justice in Chile: A Crucial Relationship - Ferrara, Anita (Human Rights Review, 2021)

Non-recurrence, reconciliation, and transitional justice: situating accountability in Northern Ireland’s oral history archive - Kinder, Eliscia (International Journal of Human Rights, 2021)

War and Women's Human Rights Museum: Archives are Key - Jihyun, Youn (Journal of Korean Society of Archives and Records Management, 2020)

Advancing Global Accountability: The Role of Universal Jurisdiction in Prosecuting International Crimes - Varney, Howard; Zduńczyk, Katarzyna (RESEARCH REPORT, 2020)

Archives and Human Rights - Boel, Jens; Canavaggio, Perrine; Quintana, Antonio González (Routledge, 2021)
Why and how can records serve as evidence of human rights violations, in particular crimes against humanity, and help the fight against impunity? Archives and Human Rights shows the close relationship between archives and human rights and discusses the emergence, at the international level, of the principles of the right to truth, justice and reparation.Through a historical overview and topical case studies from different regions of the world the book discusses how records can concretely support these principles. The current examples also demonstrate how the perception of the role of the archivist has undergone a metamorphosis in recent decades, towards the idea that archivists can and must play an active role in defending basic human rights, first and foremost by enabling access to documentation on human rights violations.Confronting painful memories of the past is a way to make the ghosts disappear and begin building a brighter, more serene future. The establishment of international justice mechanisms and the creation of truth commissions are important elements of this process. The healing begins with the acknowledgment that painful chapters are essential parts of history; archives then play a crucial role by providing evidence. This book is both a tool and an inspiration to use archives in defence of human rights. The Open Access version of this book, available at https://doi.org/10.4324/9780429054624, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.
Keywords: Archives; Human rights; Political aspects; References - Boel et al. (2021), Archives and Human Rights; References - Comma (2020 1-2), Archives and Human Rights; Transitional justice